Co-construction des capacités et des ressources territoriales dans les territoires touristiques de montagne - Jean-Christophe Dissart (Revue de Géographie Alpine)
Mass tourism in mountain resorts faces a changing context: climate change, economic crises, increased competition and changing demand. In this situation, multiple tourism projects arise, using stakeholders and resources, with a unifying reference to mountains. However, this process is not straightforward, and consequently it becomes critical to analyze the conditions that prevail in renewing tourism services in mountain areas. In other words, the critical question pertains to the shift from mass tourism to a more specific form of tourism. We make the hypothesis that by using regional generic resources, tourism creates “territorial capabilities” that are then used to build and add value to territorial resources. Tourism, in turn, builds on the latter to adapt. This “virtuous circle” of tourism is analyzed in the Oisans territory (in the Alps). First, we show how tourism has shaped this region by creating conditions for the emergence of territorial capabilities. Second, we explain how these capabilities enable a renewal of tourism services. Results show that capabilities act as human and social resources for the territory, especially with respect to the development of mountain tourism projects.